Identification of the carotenoid modifying gene PALE YELLOW PETAL 1 as an essential factor in xanthophyll esterification and yellow flower pigmentation in tomato (Solanum lycopersicum). (2nd July 2014) - Ariizumi, Tohru; Kishimoto, Sanae; Kakami, Ryo; Maoka, Takashi; Hirakawa, Hideki; Suzuki, Yutaka; Ozeki, Yuko; Shirasawa, Kenta; Bernillon, Stephane; Okabe, Yoshihiro; Moing, Annick; Asamizu, Erika; et al.
Summary Xanthophylls, the pigments responsible for yellow to red coloration, are naturally occurring carotenoid compounds in many colored tissues of plants. These pigments are esterified within the chromoplast; however, little is known about the mechanisms underlying their accumulation in flower organs. In this study, we characterized two allelic tomato (Solanum lycopersicum L.) mutants, pale yellow petal (pyp) 1‐1 and pyp1‐2, that have reduced yellow color intensity in the petals and anthers due to loss‐of‐function mutations. Carotenoid analyses showed that the yellow flower organs of wild‐type tomato contained high levels of xanthophylls that largely consisted of neoxanthin and violaxanthin esterified with myristic and/or palmitic acids. Functional disruption of PYP1 resulted in loss of xanthophyll esters, which was associated with a reduction in the total carotenoid content and disruption of normal chromoplast development. These findings suggest that xanthophyll esterification promotes the sequestration of carotenoids in the chromoplast and that accumulation of these esters is important for normal chromoplast development. Next‐generation sequencing coupled with map‐based positional cloning identified the mutant alleles responsible for the pyp1 phenotype. PYP1 most likely encodes a carotenoid modifying protein that plays a vital role in the production of xanthophyll esters in tomato anthers and petals. Our results provide insight into the molecular mechanism underlying the production of xanthophyll esters in higher plants, thereby shedding light on a longstanding mystery.